Microfluidic tank assisted nicotine sensing property of field effect transistor composed of an atomically thin MoS2 channel. Issue 47 (26th November 2020) - Mamun, Muhammad Shamim Al; Tanaka, Yudai; Waizumi, Hiroki; Takaoka, Tsuyoshi; Wang, Zhipeng; Alam, Md Iftekharul; Ando, Atsushi; Fukuyama, Mao; Hibara, Akihide; Komeda, Tadahiro
Abstract : We investigated the sensor behavior of a field effect transistor, the channel of which is made of atomically thin MoS2 layers, focusing on the interaction of the MoS2 channel with the solution containing target molecules. Abstract : We investigated the sensor behavior of a field effect transistor, the channel of which is made of atomically thin MoS2 layers, focusing on the interaction of the MoS2 channel with the solution containing target molecules. For this purpose, we made a newly designed device in which the mask covered the electrodes of the source and the drain in order to make the solution contact only with the channel. In addition, a micro-fluid tank was fabricated above the channel as a solution reservoir. We examined the FET properties of this device for the sensing of the nicotine molecule for the development of a detection system for this molecule in the human body under in vivo conditions. We detected the sensor behavior both for the drop-cast process and for the condition where the channel contacts with the solution. The drain-current vs. gate-voltage variation of the MoS2 -FET with the attachment of the nicotine molecule was clearly observed for both cases. For the latter case, the threshold voltage shifted in the negative gate-voltage direction with the increase of the concentration of the nicotine in the solution. This can be explained by the electron transfer from the molecule to the MoS2 channel, which was further confirmed by analyzing the X-ray photoemission spectroscopy and Raman spectroscopy together with the DFT calculation. The sensor can detect the variation of the nicotine concentration in the IPA solution by detecting the V th change of the MoS2 -FET.